2019
DOI: 10.1186/s12875-019-0930-y
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting general practitioners for palliative care research in primary care: real-life barriers explained

Abstract: Background The implementation of early palliative care within a primary care setting is a recent academic topic. Recruiting General Practitioners (GPs) to participate in a palliative care study can be challenging. The pro-Spinoza project implemented a Care Pathway for Primary Palliative Care in 5 areas in Belgium. During this project, the feasibility of the recruitment of GPs and palliative care patients was evaluated. Methods The recruitment process was recorded in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…This confirms the difficulties involved in recruiting GPs for PC-focussed projects. Data from a recent study reported that of 4065 eligible GPs, only 2.8% agreed to participate in a PPC research in Belgium [21]. Tailored training programmes should be implemented to encourage more GPs to take part in this type of research.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms the difficulties involved in recruiting GPs for PC-focussed projects. Data from a recent study reported that of 4065 eligible GPs, only 2.8% agreed to participate in a PPC research in Belgium [21]. Tailored training programmes should be implemented to encourage more GPs to take part in this type of research.…”
Section: Discussionmentioning
confidence: 99%
“…The focus groups were sometimes very small (twice only 3 GPs), this possibly limited their data. Elsewhere we published reasons for non-participation for the implementation part of this project [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment and data collection support strategies are described elsewhere in more detail 14 . Many GPs stated that the online data collection was difficult to handle.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…GPs who were male, single-handed and/or in their late career phase, seemed less involved in primary palliative care research activities than other GP profiles, possibly because they lacked support with data collection 14 . These preliminary findings could refine recruitment and participant monitoring strategies in primary palliative care research.…”
Section: Implications For Research And/or Practicementioning
confidence: 99%